2019
DOI: 10.1007/s00268-019-05199-1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Women Entering Surgical Careers: A Global Study into Medical Student Perceptions

Abstract: Background Barriers to female surgeons entering the field are well documented in Australia, the USA and the UK, but how generalizable these problems are to other regions remains unknown. Methods A cross-sectional survey was developed by the International Federation of Medical Students' Associations (IFMSA)'s Global Surgery Working Group assessing medical students' desire to pursue a surgical career at different stages of their medical degree. The questionnaire also included questions on students' perceptions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 21 publications
1
48
0
Order By: Relevance
“…[ 122 ] High income United States Questionnaire n = 107 100% Not reported Residency and training Year Title World Bank Income Group Country Study design Population size Gender distribution (M/F) % Female Funding source 2020 Barriers to Women Entering Surgical Careers: A Global Study into Medical Student Perceptions. [ 18 ] All levels 75 Countries ψ Questionnaire n = 639 (374/265) 59% Not reported 2020 Sexual Harassment and Cardiothoracic Surgery: #UsToo? [ 15 ] Unknown Unknown ∓ Questionnaire n = 790 (185/591) 23% Not reported 2020 Women Continue to Be Underrepresented in Surgery: A Study of AMA and ACGME Data from 2000 to 2016.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 122 ] High income United States Questionnaire n = 107 100% Not reported Residency and training Year Title World Bank Income Group Country Study design Population size Gender distribution (M/F) % Female Funding source 2020 Barriers to Women Entering Surgical Careers: A Global Study into Medical Student Perceptions. [ 18 ] All levels 75 Countries ψ Questionnaire n = 639 (374/265) 59% Not reported 2020 Sexual Harassment and Cardiothoracic Surgery: #UsToo? [ 15 ] Unknown Unknown ∓ Questionnaire n = 790 (185/591) 23% Not reported 2020 Women Continue to Be Underrepresented in Surgery: A Study of AMA and ACGME Data from 2000 to 2016.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, no literature on female surgeons was available from Central and South America, despite evidence of women working as surgeons in this region [ 82 ]. More importantly, this review has demonstrated that differences in culture, economic and educational opportunity, gender equity and women’s empowerment affect the experiences of both female surgical trainees and current female surgeons [ 3 , 18 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unconscious bias and microaggression are strongly associated with the choice to enter neurosurgical training and pursue career progression. 3 Unconscious or implicit bias are attitudes or stereotypes that affect our understanding in an unconscious manner; microaggression follows, as actions subtly and often unintentionally hostile to a minority group. Both are pervasive and present throughout life and influence perception of the likelihood of a leadership career in neurosurgery.…”
Section: Setting the Scene For Failure: Unconscious Bias And Microaggmentioning
confidence: 99%
“…Diversity in medicine and surgery is important as it leads to more inclusive and patient-centred care, increased patient compliance, satisfaction and participation in clinical trials, and greater access to care for disenfranchised communities [4]. There remains a lack of representation of minority groups in positions of leadership in surgery [5], and mentorship is a crucial factor in promoting a career in surgery [6][7][8][9][10]. Roberts SE et al found that the perceived barriers preventing African Americans from pursuing a career in surgery included 'lack of mentorship', 'difficulty finding minority role models', and 'fighting stereotypes' [11].…”
Section: Potential Long-term Impacts Of Surgical Placement Cancellationsmentioning
confidence: 99%